Online Teaching Competencies, Attitude Towards Mathematics and Academic Achievement of Grade 10 Learners in Geometry: a Path Analysis - Verben G. Simbulas; Edna T. Salva; Lolly Jean C. Simbulas (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aimed to determine the influence of online teaching competencies and attitude toward mathematics on the academic achievement of grade 10 learners in geometry. Also, it sought to find out the best fit model that would explain the academic achievement in geometry. Grade 10 learners from selected private schools that utilized online learning modality were chosen using complete enumeration. An adapted set of questionnaires were used in obtaining the data. A quantitative research design using the descriptive-correlational method was employed. The collected data were treated using the mean and standard deviation, Pearson product moment correlation, linear regression analysis, and path analysis. Findings revealed that the levels of online teaching competencies, mathematics attitude, and academic achievement in geometry were high, moderately high, and low, respectivelyFurthermore, a respecified model showing the indirect effect of the online teaching competencies on the academic achievement in geometry through the attitude towards mathematics as a mediator was found to be the best fit model for the academic achievement in geometry.